2018
DOI: 10.1186/s12936-018-2200-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of artesunate–amodiaquine, dihydroartemisinin–piperaquine and artemether–lumefantrine for the treatment of uncomplicated Plasmodium falciparum malaria in Maradi, Niger

Abstract: BackgroundMalaria endemic countries need to assess efficacy of anti-malarial treatments on a regular basis. Moreover, resistance to artemisinin that is established across mainland South-East Asia represents today a major threat to global health. Monitoring the efficacy of artemisinin-based combination therapies is of paramount importance to detect as early as possible the emergence of resistance in African countries that toll the highest burden of malaria morbidity and mortality.MethodsA WHO standard protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…Therefore, based on these data, the choice of the two artemisinin-based combinations as first-line treatment for uncomplicated P. falciparum malaria was appropriate in Burkina Faso. Efficacy of both treatment was evaluated in other sub-Saharan African countries and similar good efficacy were reported in west Africa [34][35][36][37][38], and in eastern Africa [11,39]. In the current study, both treatments were equally efficacious with however, most treatment failure observed in AL arm (8.9%).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, based on these data, the choice of the two artemisinin-based combinations as first-line treatment for uncomplicated P. falciparum malaria was appropriate in Burkina Faso. Efficacy of both treatment was evaluated in other sub-Saharan African countries and similar good efficacy were reported in west Africa [34][35][36][37][38], and in eastern Africa [11,39]. In the current study, both treatments were equally efficacious with however, most treatment failure observed in AL arm (8.9%).…”
Section: Discussionsupporting
confidence: 72%
“…By this measure, recurrent parasitaemia rates were high in both arms with however a remarkably higher rate in the AL arm (50.2%). Most studies in sub-Saharan Africa reported similar results with up to 40% of recurrent parasitaemia [35,40,42,49]. The duration of post treatment prophylaxis is however an important criterium in the choice of anti-malarial drugs, especially in areas with a high risk of re-infection.…”
Section: Discussionmentioning
confidence: 92%
“…Even in the worst case scenario, where participants with missing PCR results by day 42 were considered as treatment failures, the PCR-adjusted malaria cure rate was still > 94%. Additionally, AL achieved parasite clearance rates, similar to that in HIV-uninfected individuals [3133]. Although there was no evidence of malaria recrudescence, at least 16% of the study participants had malaria recurrence by day 42, with the majority of the re-infections occurring between days 35 and 42.…”
Section: Discussionmentioning
confidence: 62%
“…Eight studies [ 33 40 ] did not report the PCR corrected ACPR. However, except two studies [ 41 , 42 ], the rest reported PCR uncorrected ACPR and included for this group of analysis. Using meta-analysis, the PCR uncorrected ACPR of AL for the treatment of uncomplicated malaria was 87% (95% CI: 85-90%).…”
Section: Resultsmentioning
confidence: 99%